Iliofemoral technique modification using an anchor screw as treatment of canine traumatic hip luxation - case report - Rocha, A. G. [UNESP]; Costa, R. C. [UNESP]; Morato, G. O. [UNESP]; Chung, D. G. [UNESP]; Padilha-Filho, J. G. [UNESP]; Minto, B. W. [UNESP]; Dias, L. G. G. G. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
Twelve dogs with traumatic hip luxation were selected for surgical intervention with a modified iliofemoral suture technique using an anchor screw to substitute the passage of suture material through a perforated tunnel in the ilium. Six procedures were performed with non-absorbable suture and other six with absorbable suture materials. These cases were evaluated at 15, 30, 60, and 90 days after surgery by performing an ambulation analysis and palpation of the joint. In all cases, there was a return of partial and total limb support in an average of 3 and 19 postoperative, respectively. The fixation strategy of the suture material in the ilium using an anchor screw proved to be efficient with a smaller surgical approach and lesser surgical difficulty, maintaining joint congruence in acute as chronic luxation cases. The use of absorbable and non-absorbable sutures had excellent clinical results, but there was a subjective superiority of the first ones, once 4 dogs of the non-absorbable group presented some discomfort during the postoperative palpation of the joint, 90 days after surgery.
Keywords: coxofemoral joint; trauma; surgical stabilization